New strategies for solid tumor immunotherapy based on NK cells - I. G. Vorobyova; E. V. Abakushina (Медицинская иммунология, 2024)
A major issue in treatment of solid malignancies is associated with multiplicity and rapid adaptation of immunosuppressive effects exerted by immune cells reprogrammed by the tumor. Tumor-associated macrophages (TAM), neutrophils, and tumor-infiltrating lymphocytes lose their ability to protect healthy tissues and to destroy malignant cells by activating a number of tools causing blockage of immune surveillance and reduction of therapeutic effects. Immune cells attracted by chemokines and reprogrammed by the tumor supply the malignant cells with missing nutrients (e.g., by producing arginase), support the survival of de novo recruited cells at low pH (acidosis) around malignant tissues, produce increased amounts of angiogenic factors thus contributing to increased blood supply to the tumor. Productive inflammation, being among the main types of immune response, destroys tumor pathogens and moves into chronic inflammation with progression of the tumor, thus causing immune suppression. Restoration of inflammatory immune reactions after tumor resection, chemotherapy, and radiotherapy is necessary to achieve remission without relapse or, at least, increases the time period until next episode of the disease progression. Transplantation of NK cells has a number of advantages over T lymphocytes in order of restored productive inflammation. However, it also requires additional therapeutic impacts, since various mechanisms of tumor immune escape block anti-tumor immunity. To achieve a pronounced therapeutic effect, the optimal ratio is important between the activity and number of NK cells, supporting therapeutic agents, with regard of aggressiveness and spread of malignant tumor. Among the developing areas of NK cells support, one may consider the NK cell “enhancers” (NKCE), engineered proteins that make cell therapy more selective and targeted. NKCE may activate the targeted migration of NK cells, along with blockage of inhibitory ligands. Currently, the blockage of inhibitory signals is studied in order to control metastatic tumors via KIR, NKG2A, TIGIT, TIM-3, EGFR, PD1 receptors, PDL1 and NKG2D ligand, as reported in a number of clinical and preclinical trials. The increased specificity of therapy is also achieved by usage of new-generation antibodies – nanoantibodies, aimed for targeted blocking of tumor-derived exosomes (TDE), as well as protein domains that enhance targeted migration of NK cells and therapeutic nanoparticles.